Structural and dielectric properties of yttrium-substituted hydroxyapatites - Kaygili, Omer; Dorozhkin, Sergey V.; Ates, Tankut; Gursoy, N. Canan; Keser, Serhat; Yakuphanoğlu, Fahrettin; Selcuk, A. Birkan (Elsevier, 2015)
Hydroxyapatite (HAp) samples doped with 0,2 and 4 at.% of yttrium (Y) were characterized using X-ray diffraction (XRD), Fourier transform infrared (FOR) spectroscopy, scanning electron microscopy attached with energy dispersive X-ray (EDX) spectroscopy, antimicrobial activity tests and dielectric studies. The hydroxyl groups observed in FOR spectra confirmed the formation of HAp phase in the studied samples. The crystallite size, crystallinity degree and lattice parameters of the samples were changed with Y content The volume of the unit cell was gradually decreased with the addition of Y. Undoped and Y-containing HAp samples were screened to determine their in vitro antimicrobial activities against the standard strains. It was found that no samples have any antimicrobial effect. The relative dielectric permittivity and dielectric loss are affected by Y content. While the alternating current conductivity increases with increasing frequency, it decreases with increasing Y content (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Yttrium (Y); X-ray diffraction (XRD); Antimicrobial activity; Dielectric properties